Genome-wide Analysis of STAT3-Mediated Transcription during Early Human Th17 Cell Differentiation - Tripathi Subhash K; Chen Zhi; Larjo Antti; Kanduri Kartiek; Nousiainen Kari; Aijo Tarmo; Ricano-Ponce Isis; Hrdlickova Barbara; Tuomela Soile; Laajala Essi; Salo Verna; Kumar Vinod; et al. (CellPress, 2022)
The development of therapeutic strategies to combat immune-associated diseases requires the molecular mechanisms of human Th17 cell differentiation to be fully identified and understood. To investigate transcriptional control of Th17 cell differentiation, we used primary human CD4+ T cells in small interfering RNA (siRNA)-mediated gene silencing and chromatin immunoprecipitation followed by massive parallel sequencing (ChIP-seq) to identify both the early direct and indirect targets of STAT3. The integrated dataset presented in this study confirms that STAT3 is critical for transcriptional regulation of early human Th17 cell differentiation. Additionally, we found that a number of SNPs from loci associated with immune-mediated disorders were located at sites where STAT3 binds to induce Th17 cell specification. Importantly, introduction of such SNPs alters STAT3 binding in DNA affinity precipitation assays. Overall, our study provides important insights for modulating Th17-mediated pathogenic immune responses in humans.